The influence of some factors of competitiveness on business risks - Dvorsky, Jan; Kliestik, Tomas; Cepel, Martin; Strnad, Zdenek (Journal of Business Economics and Management, 2020)
The impact of significant competition factors on the riskiness of business risk in the SMEs sector in the Czech Republic and Slovak Republic. The empirical research was constructed on the basis a questionnaire. The attitudes from 641 entrepreneurs from two countries were collected during the year 2018. The statistical hypotheses were evaluated using quantitative methods. The multiple linear regression models were used to evaluate the impact of the competitive environment and of the narrow business environment on the perception of the riskiness of business risk according to entrepreneurs. The conclusions ofthe research showed an interesting finding. The authors found that the competitive environment, as well as the narrower business environment, affects the perception of the riskiness of business risk. It has also been shown that my customers accept the prices of my products and services. This is the most important indicator of a competitive environment. The most important indicator of a narrower business environment is that my customers support me in doing business. The authors believe that the article has brought several interesting findings and new incentives for the further research and discussion regarding to the perception of enterprise risk not only in the selected countries this research.